Building a neuroinfectious disease consensus curriculum. (30th July 2019) - Venkatesan, Arun; Chow, Felicia C.; Aksamit, Allen; Bartt, Russell; Bleck, Thomas P.; Jay, Cheryl; Pastula, Daniel M.; Roos, Karen L.; Rumbaugh, Jeffrey; Saylor, Deanna; Cho, Tracey A.
Abstract : Objective: To delineate a comprehensive curriculum for fellowship training in neuroinfectious diseases, we conducted a modified Delphi approach to reach consensus among 11 experts in the field. Methods: The authors invited a diverse range of experts from the American Academy of Neurology Neuro-Infectious Diseases (AAN Neuro-ID) Section to participate in a consensus process using a modified Delphi technique. Results: A comprehensive list of topics was generated with 101 initial items. Through 3 rounds of voting and discussion, a curriculum with 83 items reached consensus. Conclusions: The modified Delphi technique provides an efficient and rigorous means to reach consensus on topics requiring expert opinion. The AAN Neuro-ID section provided the pool of diverse experts, the infrastructure, and the community through which to accomplish the consensus project successfully. This process could be applied to other subspecialties and sections at the AAN.